Hydrogel implants for transscleral diffusion delivery of topotecan: In vivo proof of concept in a rabbit eye model - Hobzova, Radka; Kodetova, Martina; Pochop, Pavel; Uhlik, Jiri; Dunovska, Katerina; Svojgr, Karel; Hrabeta, Jan; Feriancikova, Barbara; Cocarta, Ana-Irina; Sirc, Jakub (International journal of pharmaceutics, 2021)
Treatment of retinoblastoma (Rb) has greatly improved in recent years in terms of survival and eye salvage rates, using mainly intra-arterial or intravitreal chemotherapy. However, the treatment of vitreous tumor seeding still represents a challenge and it is of great interest to develop new strategies to deliver pharmacologically sufficient drug amounts to the vitreous humor. In the present work, we present a lens-shaped bi-layered hydrogel implant for delivery of topotecan (TPT) via transscleral diffusion. The implant consists of an inner TPT-loaded poly(2-hydroxyethyl methacrylate) (pHEMA) layer adjacent to the sclera and an outer covering poly(2-ethoxyethyl methacrylate) (pEOEMA) layer impermeable to TPT. TPT-loaded pHEMA samples exhibit long-lasting in vitro cytotoxicity against the Rb cell line Y79. In an in vivo experiment, pHEMA/pEOEMA implants are successfully surgically administered to the posterior segment of rabbit eyes. The determination of TPT pharmacokinetics demonstrates the attainment of promising levels of TPT (10 ng/ml) in vitreous humor 8 h after implant placement. The results from the pilot experiment constitute the proof of principle for the use of the proposed implants as a drug delivery system for the local treatment of intraocular diseases.
Keywords: Topotecan; Animals; retinoblastom; Vitreous Body; Intraocular delivery; zvířata; Hydrogels; HEMA; Hydrogel; králíci; Retinal Neoplasms; Transscleral diffusion; nádory sítnice; Rabbits; topotekan; sklivec; Retinoblastoma; hydrogely